Eco-epidemiological study of an endemic Chagas disease region in northern Colombia reveals the importance of Triatoma maculata (Hemiptera: Reduviidae), dogs and Didelphis marsupialis in Trypanosoma cruzi maintenance - Omar Cantillo-Barraza; Edilson Garcés; Andrés Gómez-Palacio; Luis A. Cortés; André Pereira; Paula L. Marcet; Ana M. Jansen; Omar Triana-Chávez (Parasites & Vectors, 2015)
Abstract Background In Colombia, Rhodnius prolixus and Triatoma dimidiata are the main domestic triatomine species known to transmit T. cruzi. However, there are multiple reports of T. cruzi transmission involving secondary vectors. In this work, we carried out an eco-epidemiological study on Margarita Island, located in the Caribbean region of Colombia, where Chagas disease is associated with non-domiciliated vectors. Methods To understand the transmission dynamics of Trypanosoma cruzi in this area, we designed a comprehensive, multi-faceted study including the following: (i) entomological evaluation through a community-based insect-surveillance campaign, blood meal source determination and T. cruzi infection rate estimation in triatomine insects; (ii) serological determination of T. cruzi prevalence in children under 15 years old, as well as in domestic dogs and synanthropic mammals; (iii) evaluation of T. cruzi transmission capacity in dogs and Didelphis marsupialis, and (iv) genetic characterization of T. cruzi isolates targeting spliced-leader intergene region (SL-IR) genotypes. Results Out of the 124 triatomines collected, 94 % were Triatoma maculata, and 71.6 % of them were infected with T. cruzi. Blood-meal source analysis showed that T. maculata feeds on multiple hosts, including humans and domestic dogs. Serological analysis indicated 2 of 803 children were infected, representing a prevalence of 0.25 %. The prevalence in domestic dogs was 71.6 % (171/224). Domestic dogs might not be competent reservoir hosts, as inferred from negative T. cruzi xenodiagnosis and haemoculture tests. However, 61.5 % (8/13) of D. marsupialis, the most abundant synanthropic mammal captured, were T. cruzi-positive on xenodiagnosis and haemocultures. Conclusions This study reveals the role of peridomestic T. maculata and dogs in T. cruzi persistence in this region and presents evidence that D. marsupialis are a reservoir mediating peridomestic-zoonotic cycles. This picture reflects the complexity of the transmission dynamics of T. cruzi in an endemic area with non-domiciliated vectors where active human infection exists. There is an ongoing need to control peridomestic T. maculata populations and to implement continuous reservoir surveillance strategies with community participation.